Clinical Findings Arising from the Use of Silver Diamine Fluoride to Prevent or Treat Caries Lesions and Dentinal Hypersensitivity: A Data Mining Analysis - Gabriella Fernandes Rodrigues; Lucas Alves Jural; Mariana Leonel Martins; Ana Lúcia Vollú; José Vicente-Gomila; Lucianne Cople Maia; Ivo Carlos Corrêa; Fernanda Barja-Fidalgo; Andréa Fonseca-Gonçalves (Association of Support to Oral Health Research (APESB), 2024)
Objective: To summarize data of clinical trials that used silver diamine fluoride (SDF) to prevent and treat caries lesions and dentinal hypersensitivity. Material and Methods: Six electronic databases were searched in May 2022. The concentration of SDF, type of usage (alone/combined), dentition, anterior/posterior teeth, tooth region, dental tissue, number of the treated surfaces, the intervention environment, participants' age, frequency and duration of SDF application, purpose, and outcome were the extracted variables. The type of study, year of publication, authors, journals, and country were also investigated. Results: From 8860 articles, 53 were selected. Most were randomized (n=38), that applied 38% SDF (n=43), alone (n=44), on multiple surfaces (n=44), only in dentin (n=36), of the crown (n=46) of anterior and posterior (n=36) primary teeth (n=39). The studies were preferably carried out outside the clinic (n=31), only in children (n=33), with reapplication of SDF (n=30), but did not inform the duration of application (n=19). SDF was most used to treat (n=46) only caries lesions (n=50). They were published between 2001 and 2022, mainly in the Journal of Dentistry (n=10). China (n=19) and Lo E.C.M (n=19) were the countries and authors that published the most, respectively. Conclusion: The silver diamine fluoride 38% alone was most used to treat caries lesions in the dentin of the crown of all primary teeth, preferably applied on multiple surfaces, requiring reapplication, and outside the clinic.